Modified xiaoyao san combined with chemotherapy for breast cancer: A systematic review and meta-analysis of randomized controlled trials - Pan, Junhua; Fu, Shunlian; Zhou, Qian; Lin, Dajun; Chen, Qiu (Frontiers in Oncology, 2023)
Background Breast cancer is a common cause of cancer-related death worldwide. Chemotherapy plays an indispensable role in the conventional treatment of breast cancer, bringing some physical burdens and discomfort on cancer patients. Consequently, more and more patients turn to seeking the help of Complementary and Alternative Medicine (CAM), mainly traditional Chinese medicine (TCM). Xiaoyao san (XYS), a classical formula, has been shown to improve symptoms of breast cancer. An increasing number of researches suggest that compared to chemotherapy alone, Chinese herbal medicine combined with chemotherapy could increase effectiveness and reduce toxicity caused by chemotherapy. Emerging experimental research continuously demonstrated some of the components in XYS could stop breast cancer tumor cells from growing. However, the efficacy and safety of modified XYS combined with chemotherapy remain to be determined. Therefore, it is essential to evaluate the comparative effectiveness and safety of modified XYS combined with chemotherapy in-depth, thus providing clinicians and policymakers with evidence-based guidance and new treatment options. Objective To comprehensively evaluate the efficacy and safety of modified XYS in conjunction with chemotherapy in treating breast cancer by conducting a meta-analysis. Methods 8 databases were systemically searched until April 3, 2022, including Web of Science PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure (CNKI), Wanfang, Chinese Scientific Journals Database (VIP), and Chinese Biological Medical Database (CBM). Relevant randomized controlled trials (RCTs) comparing modified XYS in combination with chemotherapy versus chemotherapy alone were included. For the evaluation of methodological quality, Cochrane Collaboration was considered. Software Review Manager (version 5.4) was used for data analysis. Software STATA (version 15.0) was employed for sensitivity analysis and publication bias. Results Altogether, 17 RCTs involving 1207 patients were investigated in the current review. The findings revealed that modified XYS combined with chemotherapy could lead to beneficial improvements compared to chemotherapy alone. More specifically, the combined therapy could enhance the short-term efficacy in the treatment of solid tumors (OR: 1.74; 95% CI 1.27 to 2.39; P = 0.0006; I2 = 0%); improve QOL (quality of life) (OR: 3.75; 95% CI 2.58 to 5.44; P < 0.00001; I2 = 0%); reduce clinical symptoms (OR: 3.69; 95% CI 1.43 to 9.49; P = 0.007; I2 = 53%); ease depression (MD: -12.96; 95% CI -16.09 to -9.83; P < 0.00001; I2 = 0%); increase leukocytes (OR: 0.32; 95% CI 0.20 to 0.50; P < 0.00001; I2 = 0%) and platelets (OR: 0.37; 95% CI 0.20 to 0.67; P = 0.001; I2 = 0%); reduce nausea and vomiting (OR: 0.26; 95% CI 0.15 to 0.44; P < 0. 00001; I2 = 0%); mitigate cardiotoxicity (OR: 0.16; 95% CI 0.07 to 0.36; P<0.00001; I2 = 0%); prolong survival time (OR: 2.19; 95% CI 1.03 to 4.66; P = 0.04; I2 = 0%), compared to chemotherapy alone. Unfortunately, there was no statistically significant difference in damage to the liver and kidney (OR: 0.59; 95% CI 0.29 to 1.21; P = 0.15; I2 = 0%). Conclusion The existing evidence suggests modified XYS combined with chemotherapy leads to beneficial improvements in the management of breast cancer, which may serve as a promising therapy for breast cancer in clinical practice. Given the limited number of high quality RCTs, more rigorous, scientific, double-blinded, large-scale, multi-center clinical trials are warranted further. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022357860.